The dynamics of relational quality in co-development alliances - Francis Bidault (European School of Management and Technology (ESMT), 2012)
Co-development alliances are formed to create new capabilities (technologies, products, services, processes, etc.) that partner organizations need in order to reach their goals. They involve the combination of competencies, and other intangible assets. These alliances typically face a high level of risks in terms of undesired leakages of confidential knowledge or failure to achieve the expected development. Relational quality, an important consideration in all alliances, is particularly key. Without it, partners might not be open enough to combine their knowledge effectively with the partners'. This article proposes a framework for defining, assessing, and monitoring relational quality in co-development alliances.
urn:nbn:de:101:1-201303269139
Keywords: 650; alliances; creative collaboration; innovation management; technology management; new product management; co-development; joint innovation